Nosocomial infections caused by community-associated methicillin-resistant Staphylococcus aureus in Colombia (2010)
Background: Community-associated methicillin-resistant Staphylococcus aureus strains (CA-MRSA) have emerged as the causative agent of health care-associated infections. Methods: An observational and prospective study was carried out in 5 hospitals in Bogota´, Colombia; severe MRSA infections were identified, and their origin led to classification as health care-associated (HA-MRSA), community-associated, or nosocomial infections. MRSA isolates were analyzed by SCCmec, pulsed-field gel electrophoresis, multilocus sequence typing, and virulence factors. Results: Twenty-six (10.4%) CA-MRSA nosocomial infection-causing strains (eg, USA300) were detected in 250 MRSA infection isolates in mainly primary bacteremia and surgical site infections. The mortality related to nosocomial infection by CA-MRSAwas 27%. Conclusion: The presence of nosocomial infection by CA-MRSA in Colombia was confirmed